Clinical evaluation of the retention of four different pit and fissure sealants on the first permanent molars - An original research - Laleena Rajkumari; Rajnish K Verma; M Rajmohan; Radhika Thakkar; Ipseeta Menon; Sandeep Kumar (Wolters Kluwer Medknow Publications, 2024)
Objective: In this study, the retention rates of four different pit and fissure sealant materials on the first permanent molars were clinically assessed and compared. Materials and Methods: A total of 120 kids aged 7 to 10 participated in a randomized controlled experiment. On their first permanent teeth, the subjects each got one of the four sealant materials (A, B, C, or D). Over the course of 24 months, the retention rates were evaluated every 6 months. The Chi-square test and Kaplan-Meier survival analysis were used for statistical analysis. Results: At 6, 12, 18, and 24 months, the following retention rates were observed overall: A (85%, 78%, 65%, 52%), B (90%, 82%, 70%, 60%), C (78%, 70%, 55%, 42%), and D (95%, 88%, 75%, 62%). At each time point, the sealant materials showed significant variations in retention rates (P 0.05). While sealants A and C showed lower retention rates, sealant D showed the best retention rates, followed by sealant B. Conclusion: This study shows that different materials have different retention rates for pit and fissure sealants on first permanent molars. Higher retention rates for sealants D and B suggest that they may be superior than sealants A and C. These results highlight how crucial it is to choose the right sealant materials to guarantee long-term retention and effectiveness in avoiding dental cavities.